The Effect of Perception on Focus Level and Satisfaction when Reading Books at Book Cafe in Bandung City - Aini, Ken; Maharani, Yuni; Vidyarini, Etika (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study examines how lighting perception influences reading focus and satisfaction in book cafés in Bandung, Indonesia. A descriptive quantitative approach was employed, involving a preference survey and an experimental study conducted at a selected book café. Thirteen female participants were assigned to three distinct seating areas characterized by different lighting conditions. Participants completed reading tasks and evaluated their environmental comfort, focus level, and reading satisfaction. The findings indicate that lighting comfort significantly correlates with focus (ρ = .000, p < .01) and reading satisfaction (ρ = .016, p < .05), although focus and satisfaction were not significantly related. ANOVA results revealed a significant difference in perceived lighting comfort across seating points, with the most favorable conditions found at Point A. These results underscore the importance of lighting design in enhancing the reading experience in multifunctional public spaces such as book cafés. Future research should consider additional environmental variables, including noise and thermal comfort.